Assessing habitat outcomes of floodplain forest restoration: case study at the Ouse Valley Park - Perez Linde, Natalia (Cranfield University, 2016)
The research project for this PhD set out to provide a best practice example of bringing together industry (Hanson Heidelberg Cement Group), a charitable body (The Parks Trust), non-departmental public body (Environment Agency) and academia (Cranfield University). The Parks Trust (landowner) and Hanson (quarry operator) worked together with the vision of creating a new floodplain forest landscape along a 1 km reach of the River Great Ouse following extraction of gravels from the site. It was the first project of its kind in the United Kingdom where planning permission was obtained specifically for the creation of a floodplain forest habitats post quarrying. The aim of the PhD research was to determine appropriate ecological approaches to apply to the assessment and future monitoring of habitat outcomes of a floodplain forest restoration project at a mineral extraction site. A central element of the research was the design of a scientifically justified monitoring programme, with key variables determined being: soil characteristics, water quality, vegetation development, site topography and water table level data. An Adaptive Monitoring Framework (AMF) was chosen to set the proposed monitoring within which was complemented with the hypothesis - The ratio of wet/dry vegetation within the floodplain forest is determined by the site topography and water table level. The hypothesis was tested by analysis of the key variables through fieldwork and existing data sources supplemented with a study of the water table level interaction with two typical floodplain forest tree species (Salix viminalis and Populus trichocarpa x deltoides) in a glasshouse experiment. Findings from the field and experimental research were then used within a spatially based landscape ecology scenario approach to identify the most suitable areas of the study site for specific species planting according to soil-water levels and topography in the floodplain forest. Outputs of this research enhance understanding of the key aspects to consider when assessing floodplain forest re-creation/restoration and enable guidelines and recommendations to be developed for land managers based on a long-term and an adaptive ecological monitoring approach. These management guidelines and recommendations based on a systematic scientific approach applied within the research should be appropriate to other similar restoration projects. The research provides the background evidence on what should be measured to determine the environmental changes of the floodplain forest habitat restoration as it develops towards restoration success.
Keywords: Water table level; topography; Adaptive Monitoring Framework; AMF; Restoration success; Landscape approach; Novel ecosystem